El Teatro del Oprimido utilizado como práctica de aula para la apropiación de las competencias ciudadanas en estudiantes de grados 8° de la institución educativa Regional Simón Bolívar. (2020)
This study had as a general objective, to implement in the classroom practices the didactic sequence based on the Theater of the Oppressed for the appropriation of citizenship competences in the eighth (8th) grade students of the Headquarters of the Simón Bolívar Regional Educational Institution, from the San Antonio de los Caballeros township, Florida municipality, Valle It is a study. and the research focus is qualitative, supported by action-participation research and observation; The study was applied to 40 eighth grade students (8) from the Simón Bolívar Regional Educational Institution, to whom a survey (questionnaire) was applied. The eighth group was taken as a study group. The results obtained show that the playful activities through the techniques of the Theater of the Oppressed (Boal, 1980) applied through a didactic sequence contributed to modify the classroom practices and improve the emotional, argumentative and participative aspects in the students. The achievements achieved with said competences were: change in the conduct of classes, improvement in coexistence with peers and family, teamwork, agreements to resolve a conflict or social problem, ability to generate various alternative solutions, exercise of the citizenship; and communication through other systems such as theater using forum theater techniques and the processing and understanding of information. Therefore, it is concluded that the different techniques of the Theater of the Oppressed can be used as a ludic activity to strengthen citizenship competencies and the teacher to implement new strategies that allow transforming their pedagogical work. Keywords: "Theater of the Oppressed", citizen competences, pedagogical strategy, didactic sequence.